Experiences of healthcare workers following occupational exposure to COVID‐19 at the early stages of the pandemic: A phenomenological qualitative study - Qun Wang; Peiqin He; Yu Tian; Yimin Zhu; Yuelan Qin; Xiaoying Qiu; Yanhui Liu; Xiaoping Xu; Wanqin Hu; Zeya Shi (Wiley, 2023)
Abstract Aim To explore the experiences of healthcare workers (HCWs) following occupational exposure to coronavirus disease 2019 (COVID‐19) during the early stage of the pandemic. Design A Husserl descriptive phenomenological study design was employed. Methods Convenient and snowball sampling was used. In‐depth semi‐structured telephone interviews were conducted from February to March 2020 with the frontline HCWs who were exposed to COVID‐19 during work. Data analysis was conducted following the 7‐step analysis method developed by Colaizzi. Results Fifteen HCWs participated in the study. Four themes were identified, including (1) traumatic experiences since the occupational exposure; (2) getting through the hard time; (3) struggling to return to work; (4) reflections on occupational exposures. Conclusion The HCWs had traumatic and painful experiences after the occupational exposure. But they returned to work with strong resilience, professional obligation and social support. Training and supervision, and adequate supply of personal protective equipment are suggested to prevent professional exposure. Social and organizational support should be provided for the exposed HCWs.